An anatomically accurate dielectric profile of the porcine kidney. (26th February 2018) - Salahuddin, Saqib; Gioia, Alessandra La; Shahzad, Atif; Elahi, Muhammad Adnan; Kumar, Arun; Kilroy, David; Porter, Emily; O'Halloran, Martin
Abstract: Microwave ablation is a promising treatment for kidney cancer. Accurate knowledge of the dielectric properties of biological tissues is vital for quantifying the safety, reliability and accuracy of ablation, among other microwave medical treatments and diagnostic technologies. In dielectric studies to date, the heterogeneity within the kidney has not been considered, and the kidney has been treated as a fully homogeneous organ. Therefore, the available dielectric data of the kidney is not as thorough and accurate as it could be. For this reason, in this study, dielectric measurements are performed over a broad frequency range to quantitatively investigate the difference between the dielectric properties of various regions of the kidney and to develop an anatomically accurate dielectric profile of the kidney. All measurements are conducted on freshly excised porcine kidney samples, and confounders impacting dielectric data are controlled and related metadata recorded. The results demonstrate a considerable difference of up to 49% between the dielectric properties of different regions of the kidney. The findings in this paper suggest that the heterogeneity within the kidney should be taken into consideration in order to obtain an accurate representation of the actual dielectric properties. Additionally, a two-pole Cole-Cole model is fitted to the measured data of the different regions of the kidney and the model parameters presented for reference. The anatomically accurate dielectric profile of kidney provided in this paper will support the development of more effective and reliable microwave medical treatments.